Numerical Analysis Study on the Influence of Shield Cutting Pile on the Settlement of Pile–Soil Composite Foundation - Ming-ming Cao; Shi-ju Ma; Jing-wei Zhang (Advances in Civil Engineering)
Based on the shield cutting pile–soil composite foundation project of Zhengzhou Metro Line 5, numerical analysis was employed to replicate the in situ experimental conditions on site. The study focused on investigating the impact of shield cutting piles on the settlement of pile–soil composite foundation and analyzing the sensitivity of shield construction parameters, face pressure (P), and grouting pressure (Q). Comparing the numerical analysis results of land surface subsidence with field in situ test monitoring results reveals a consistent pattern, validating the rationality of the numerical modeling method presented in this paper. The results demonstrate that the vertical displacement of the formation caused by shield cutting pile construction can be divided into settlement and uplift areas. The region with significant formation displacement settlement spans within 0.9D (5.4 m above the tunnel vault), whereas the area with pronounced formation displacement uplift ranges within 0.58D (3.5 m below the tunnel arch bottom). The influence of face pressure (P) on the bearing characteristics of the composite foundation primarily occurs during the prepile cutting stage, whereas the influence of grouting pressure (Q) on the bearing characteristics of the composite foundation mainly manifests after the shield tail separates from the residual pile of the composite foundation.